2021
DOI: 10.1080/17518423.2020.1858359
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Exergames for Children with Cerebral Palsy following Lower Extremity Orthopedic Surgery: A Feasibility Study

Abstract: Objective: Evaluate the feasibility of implementing cycling-based exergames for children with cerebral palsy (CP) following lower extremity orthopedic surgery and explore its impact on pain and well-being. Methods: Ten children with CP were recruited; the first five received physiotherapy (comparison) and next five received fifteen exergame sessions over 3 weeks and physiotherapy (case) (NCT0376907). Feasibility indicators evaluated recruitment, questionnaire and exergame completion. Faces Pain Scale-Revised (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…They reported that they would choose to participate in sports within the real environment and that their engagement with exergames motivated them to get involved with new sports. Similarly, Cardenas et al (2021) supported that the inclusion of exergames is possible within the therapy of children with CP. In the same line, Macintosh et al (2017) examined the use of exergames on individuals with CP and may improve pain and wellness.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…They reported that they would choose to participate in sports within the real environment and that their engagement with exergames motivated them to get involved with new sports. Similarly, Cardenas et al (2021) supported that the inclusion of exergames is possible within the therapy of children with CP. In the same line, Macintosh et al (2017) examined the use of exergames on individuals with CP and may improve pain and wellness.…”
Section: Discussionmentioning
confidence: 83%
“…A recent study (Cardenas et al, 2021) assessed the possibility to use a cycling-based exergame for children with CP, following an orthopedic operation of the lower limbs and investigated its effect on pain and wellness. For this reason, a group of clinicians and computer scientists designed the Liberi Exergame especially for children with CP, who were ambulatory and functioning at Gross Motor Functional Classification Scale (GMFCS) I-III.…”
Section: Cerebral Palsy (Cp)mentioning
confidence: 99%
“…This supports the trend of increased conduct and publication of systematic reviews over the past 10 years, where nearly 80 reviews are published each day ( 13 ). Remarkably, in the past 10 years, only 4 non-randomized ( 14–17 ) and 7 randomized-controlled trials ( 18–24 ) have been published on the surgical management of CP-related orthopedic conditions. This highlights the need for more robust evidence to be conducted in order to determine the superiority of one surgical technique over others in correcting some of the orthopedic deformities in CP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although COPM and JTHFT are not diagnosis specific to CP, they have been utilized to evaluate CP patients over time [74,75]. PROMIS has also been utilized for CP patient evaluation [76]. The Hand Assessment for Infants (HAI) is used to describe unilateral hand function in CP patients by quantifying the contribution of each hand separately and together during a 10-15-minute play session with specific toys eliciting a wide range of motor actions [77].…”
Section: Obpp Evaluation Contrasted With Cp Evaluationmentioning
confidence: 99%